Stay time and motivational factors for bodybuilding practice in São Luís - Maranhão - Martins, Gabriel Mario Pinto (2024)
Strength training helps to improve health by preventing and treating chronic and psychological diseases, as well as promoting aesthetic changes. However, these benefits are only sustained if the individual maintains regular training. In this study, we investigated the average duration of strength training practice and the motivational factors associated with it, stratified by gender, age group, and length of experience. A total of 327 volunteers (185 men and 142 women) of various age groups completed a self-administered questionnaire containing questions related to practice time and motivational factors. The results showed that most practitioners (68.0%) had up to 12 months of strength training experience. Health was identified as the main motivational factor, followed by self-esteem and physical performance. Additionally, it was observed that most men and women remained in strength training practice for up to six months (60.5% and 53.6%, respectively) to one year (68.1% and 58.9%, respectively). Self-esteem was also identified as a significant motivational factor, especially for practitioners aged 41 or older. In conclusion, most strength training practitioners trained for 1 to 3 months, and the pursuit of health was the most relevant motivational factor among practitioners of different age groups and practice periods.